Comorbidities increase the risk of severity and mortality in COVID-19 patients: a systematic review and meta-analysis - Moura, Edilson Leite de (2021)
Introduction: Several studies have shown that patients with comorbidities present a poor clinical outcome of COVID-19, but the conclusions are not yet consolidated. We conducted a meta-analysis to evaluate the relationship between the preexistent conditions (comorbidities) in patients infected with SARS-CoV-2 and the outcome of COVID-19. Methods: PubMed, Science Direct, ISI Web of Science and Scopus databases were examined up to November 2020. We calculated the pooled odds ratio (OR) with 95% confidence interval, using fixed-effects or random-effects models. Results: A total of 48 retrospective cohort studies with 344,290 COVID-19 patients were included in the meta-analysis. The pooled results showed that hypertension, diabetes, cardiovascular, chronic pulmonary, chronic kidney and cerebrovascular diseases increase the risk of severity and mortality in COVID-19 patients. Moreover, malignancy was associated with an increased risk of death from COVID-19. Conclusions: The comorbidities previously mentioned may be important predictors of poor outcome of COVID-19, contributing to the prognosis of severe cases of the disease.